Telomeric Double Strand Breaks in G1 Human Cells Facilitate Formation of 5′ C-Rich Overhangs and Recruitment of TERRA - Nelson, Christopher B.; Alturki, Taghreed M.; Luxton, Jared J.; Taylor, Lynn E.; Maranon, David G.; Muraki, Keiko; Murnane, John P.; Bailey, Susan M. (Frontiers in Genetics, 2021)
Telomeres, repetitive nucleoprotein complexes that protect chromosomal termini and prevent them from activating inappropriate DNA damage responses (DDRs), shorten with cell division and thus with aging. Here, we characterized the human cellular response to targeted telomeric double-strand breaks (DSBs) in telomerase positive and telomerase-independent Alternative Lengthening of Telomeres (ALT) cells, specifically in G1 phase. Telomeric DSBs in human G1 cells elicited early signatures of a DDR, however, localization of 53BP1, an important regulator of resection at broken ends, was not observed at telomeric break sites. Consistent with this finding and previously reported repression of classical non-homologous end-joining (c-NHEJ) at telomeres, evidence for c-NHEJ was also lacking. Likewise, no evidence of homologous recombination (HR)-dependent repair of telomeric DSBs in G1 was observed. Rather, and supportive of rapid truncation events, telomeric DSBs in G1 human cells facilitated formation of extensive tracks of resected 5’ C-rich telomeric single-stranded (ss)DNA, a previously proposed marker of the recombination dependent ALT pathway. Indeed, induction of telomeric DSBs in human ALT cells resulted in significant increases in 5’ C-rich (ss)telomeric DNA in G1, which rather than RPA, was bound by the complementary telomeric RNA, TERRA, presumably to protect these exposed ends so that they persist into S/G2 for telomerase-mediated or HR-dependent elongation, while also circumventing conventional repair pathways. Results demonstrate the remarkable adaptability of telomeres, and thus they have important implications for persistent telomeric DNA damage in normal human G1/G0 cells (e.g., lymphocytes), as well as for therapeutically relevant targets to improve treatment of ALT-positive tumors.